Design Of A Cocoa Bean Grinding Machine With 0.5 Hp Power - Pramadya Ragatna Silalahi; Winfronstein Naibaho; Azarya Siahaan (International Journal of Technology and Education Research, 2026)
This study aims to describe the design and construction of a cocoa bean grinding machine with a power of 0.5 hp. Based on the results of the cocoa bean grinding machine performance test and simple linear regression statistical data analysis using SPSS software in Chapter IV, several conclusions can be drawn as follows: Performance and Grinding Capacity of the Machine The grinding machine has a stable performance in producing fine products at a grinding duration of 2 minutes. At a variation of 1000 grams of input load, it produces an average of 358.33 grams of fine products, a 2000 gram load produces 733.33 grams, and a 3000 gram load produces 1066.67 grams. The Effect of Material Weight on Grinding Results (Regression Analysis): Fine Results: The weight of cocoa bean input has a positive and significant effect on fine results. Every 1 gram increase in cocoa weight will increase the fine results by 0.354 grams. Coarse Results: The weight of cocoa bean input has a positive and very significant effect on coarse results. Every 1 gram increase in cocoa weight causes an increase in coarse results by 0.642 grams. This shows that the majority of additional loads will tend to increase the coarse fraction if the grinding time is limited to only 2 minutes. Unmilled Material: The weight of cocoa bean input does not significantly affect the amount of unmilled material 0.212 > 0.05. The amount of unmilled material tends to be constant at an average value of 325 to 333 grams, which indicates the existence of a certain mechanical limit/dead space in the machine's grinding chamber. Machine Noise Level: The machine operates with a high noise level, ranging from 96.6 dB to 99.5 dB, which has exceeded the safe threshold for human hearing for long duration (85 dB). Based on the regression analysis, the addition of material weight has a negative coefficient (-0.001) which means it slightly dampens the sound, but the effect of this material weight addition is statistically insignificant (0.208 > 0.05).